FREQUENCY OF OBESE PEOPLE AT HIGH RISK FOR DEVELOPING OBSTRUCTIVE SLEEP APNEA; A CROSS-SECTIONAL SURVEY - Komal Atta; Raza Ahmad; Ayesha Nawaz; Iqra Ishtiaq; Muhammad Farooq (Journal of University Medical & Dental College, 2020)
ABSTRACT BACKGROUND & OBJECTIVE: Obstructive sleep apnea (OSA) leads to multiple complications which may be life-threatening. In this study we determined the frequency of obese individuals at high risk for developing (OSA). METHODOLOGY: It was a cross-sectional survey. The study was conducted in the Medicine department of Services hospital, Lahore from February 6, 2016 to August 5, 2016. A sample size of 300 healthy obese individuals (BMI ≥ 30kg/m2) aged between 18-60 years who were accompanying a patient or visiting someone admitted, were enrolled in our study. Informed Verbal consent was obtained before administering a structured, validated questionnaire to the significant obese population; Survey was translated into Urdu for ease. The data were stratified for age, gender and BMI of the patients to control the effect modifiers. Post-stratification Chi-square test was used. A p-value ≤ 0.05 was taken as significant. RESULTS: A total of 300 subjects were enrolled. Mean age was calculated as 41.81±11.98 years, while 161(53.7%) individuals were females and 139(46.3%) were males. The frequency of risk of OSA was low in 241(80.3%) and high in 59(19.7%) of the population. The relationships of OSA with age groups and BMI were insignificant with p-value being 0.867 and 0.790 respectively. CONCLUSION: In this study, a significant population of male obese individuals was found to be at high risk for obstructive sleep apnea.